Indigenous-language communication as an opportunity for engagement in the aquatic sciences - William Chapman; Gordon Francis; Joshua Kurek (FACETS)
Knowledge gained from the aquatic sciences is of relevance to Indigenous communities. Efforts are underway to braid Indigenous and western ways of knowing, following an overdue increased focus on reconciliation and calls to action. While many collaborative projects involve informal Indigenous-language communicative outputs, the case has been made for Indigenous-language communication outputs from scientific projects that are not essentially collaborative. Here, we describe our recent efforts to communicate relevant aquatic science topics from originally non-collaborative projects in Mi'kmaw, an Indigenous language of eastern North America. We created an infographic that details the mercury cycle in Mi'kmaw by coining or reworking terms, avoiding technical language that is known to hinder science communication. This kind of knowledge mobilization shows that it is possible to communicate scientific findings in an Indigenous language to engage with an Indigenous audience. The benefits gained from doing this include addressing calls to action, language revitalization, and better inclusion, motivation, engagement, and understanding among Indigenous language speakers. In demonstrating the benefits of this type of science communication in projects not originally designed with two knowledge systems in mind, through the example of the mercury cycle, we hope that other such projects may incorporate Indigenous language into their collaborations.